Private Equity and Venture Capital Theory, Evolution and Valuation - Gallo, Serena; Verdoliva, Vincenzo (Cham : Springer International Publishing : Imprint: Springer, 2022)
The terms venture capital and private equity may differ across countries. This book discusses venture capital not only as risk capital toward unlisted companies with the aim to enhance the investee firm, but also analyses broader forms of entrepreneurial investment: from early stage financing to buyout and turnaround transaction. This book is divided into four sections. The first section aims to shed light on the terminology and offers a comparison between private equity/venture capital, and the traditional banking sector as financing sources. The second section details the differences between private equity and venture capital transactions on the basis of firm life cycle, and summarizes the main characteristics of both private equity and venture capital investors and investee firms. The third section illustrates the evolution of the private equity and venture capital industry before and after the financial crisis by looking at three fundamental aspects: fundraising, investment and divestment, all in terms of volume and trends. The last section discusses the basic elements of corporate valuation applied to private equity and venture capital industry, with some practical examples.
Chapter 1. Theoretical Background -- Chapter 2. Start-up, Expansion and Buy-out Financing -- Chapter 3. A Snapshot of Private Equity and Venture Capital Industry: Pre and Post-crisis -- Chapter 4. Highlights of Private Equity and Venture Capital Valuation.
Keywords: New business enterprises-Finance.; Valuation; Capital market; Business enterprises-Finance.; Financial services industry; Entrepreneurial Finance; Investment Appraisal; Capital Markets; Corporate Finance; Financial Services